Measurement of Snow Physical Properties and Stable Isotope Variations in the Canadian Sub-Arctic and Arctic Snowpack. Issue 3 (27th May 2021) - Levasseur, Simon; Brown, Kristina; Langlois, Alexandre; McLennan, Donald
ABSTRACT: In northern Canada, the annual peak in river discharge is dominated by the seasonal input of snowmelt. As such, climatic changes that alter snowmelt properties and timing will have cascading impacts on the hydrological system as the Arctic warms. Geochemical tracers provide a tool to characterize the various processes governing the seasonal evolution of the snowpack; however, a lack of snow observations from a variety of Arctic landscapes limits the broad applicability of such tracers and further impedes our understanding of the various processes governing snowpack evolution and its ultimate contribution to the spring discharge peak. This study aims to gain a better understanding of the spatial distribution and the temporal evolution of the natural stable isotope signatures of snow from two distinct ecoregions: open tundra and taiga. More specifically, we describe the geophysical and stable isotope properties of the snow cover at Wekweètì (Northwest Territories), a high sub-Arctic taiga site, and within the Greiner Lake Watershed, near Cambridge Bay (Nunavut), an open Arctic tundra site. Results illustrate a link between snowpack formation and stable isotope distributions at both study sites. Stable oxygen isotope ratios of snow ( δ 18 O-H2 O) show a wide range from −41‰ to −17‰ across all snow depth classes; however, heavy isotope enrichment is clearly visible in the bottom snow layers at both sites. Vapour flux from the ground under a strong temperature gradient is considered to be the main driver for this enrichment due to kinetic metamorphism, which is more prominent at the open tundra site. The stable isotope signatures of the bottom hoar layers during winter were found to be similar to river water values sampled during spring and summer, highlighting the need for more in-depth hydrological cycle assessment.